Solid electrolyte and preparation method and application thereof
By introducing a high-coverage inorganic coating layer on the surface of the solid electrolyte matrix, the problem of insufficient stability and ionic conductivity retention of solid electrolyte is solved, and the specific capacity of the battery and the first-time Coulomb efficiency are significantly improved.
Patent Information
- Application Number
- CN202510112253.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-23
- Publication Date
- 2025-05-02
AI Technical Summary
Existing solid electrolytes have shortcomings in stability and ionic conductivity retention, resulting in low specific capacity and first-time Coulomb efficiency of the battery.
By introducing a cladding layer on the surface of the solid electrolyte matrix, an inorganic substance with a sublimation temperature of less than 500°C is used as the cladding material, with a cladding rate greater than or equal to 90% to improve the stability and ionic conductivity retention of the solid electrolyte.
This method effectively reduces the interface impedance between the solid electrolyte and the electrode material, fills in the microscopic defects and pores on the surface of the solid electrolyte matrix, and improves the specific capacity of the battery and the first-time Coulomb efficiency.
Smart Images

Figure CN119920963A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of batteries, and in particular relates to a solid electrolyte and a preparation method and application thereof. Background Art
[0002] Although traditional liquid electrolytes have been widely used in batteries and other energy storage devices, their inherent safety issues (such as leakage, flammability, and thermal runaway) limit their development in high energy density and high safety applications. The emergence of solid electrolytes provides a new way to solve these problems.
[0003] However, the solid electrolytes in the prior art still have the problems of poor stability and low ion conductivity retention, which leads to low specific capacity and first coulombic efficiency of the battery. Summary of the invention
[0004] The main purpose of the present invention is to provide a solid electrolyte, which has good stability and high ion conductivity retention rate. When applied to a battery, the specific capacity and the first coulombic efficiency of the battery can be improved.
[0005] The present invention also provides a method for preparing a solid electrolyte, which can prepare the above-mentioned solid electrolyte and has simple process and low cost.
[0006] The present invention also provides a positive electrode sheet, comprising the above-mentioned solid electrolyte. Therefore, the positive electrode sheet is applied to a battery to improve the specific capacity and the first coulombic efficiency of the battery.
[0007] The present invention also provides a battery, comprising the solid electrolyte or the positive electrode sheet, so that the battery has excellent specific capacity and first coulombic efficiency.
[0008] In a first aspect, the present invention provides a solid electrolyte, comprising a solid electrolyte matrix and a coating layer present on the surface of the solid electrolyte matrix, wherein the coating layer comprises an inorganic substance having a sublimation temperature of less than 500° C.;
[0009] The coverage rate of the solid electrolyte is greater than or equal to 90%.
[0010] In the solid electrolyte as described above, the coating layer has a thickness of 0.1 nm-100 nm, preferably 2 nm-20 nm.
[0011] In the solid electrolyte as described above, the electronegativity of the bonding elements in the inorganic substance is 2.0-2.8.
[0012] In the solid electrolyte as described above, the coating layer includes elemental sulfur.
[0013] In the solid electrolyte as described above, the solid electrolyte matrix comprises a halide solid electrolyte.
[0014] The solid electrolyte as described above, the chemical composition of the halide solid electrolyte is Li a MX b , wherein M is selected from at least one of Mg, Al, Ga, In, Sb, Bi, Y, Sc, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Zr, Hf, Cr, Fe, Zn and Cd, X is selected from at least one of Cl, Br, I and F, 1≤a≤3, 1≤b≤6.
[0015] The solid electrolyte as described above, wherein M is selected from at least one of Ga, In, Y, Sc, Ho, Yb, Lu, Zr and Hf;
[0016] And / or, X is selected from Cl and / or Br.
[0017] In the solid electrolyte as described above, the difference between the binding energy between the elements of the inorganic substance and the binding energy between the elements of the inorganic substance and the elements of the solid electrolyte matrix is 0.1 eV-2.0 eV.
[0018] The solid electrolyte as described above, wherein the ionic conductivity of the solid electrolyte is greater than 0.3 mS / cm.
[0019] In a second aspect, the present invention provides a method for preparing the solid electrolyte as described above, comprising the following steps:
[0020] Heat treating a raw material system including a solid electrolyte matrix and a coating source, and obtaining the solid electrolyte after cooling;
[0021] wherein, the temperature of the heat treatment is greater than the sublimation temperature of the coating source;
[0022] The mass ratio of the solid electrolyte matrix to the coating source is (100-1000):1.
[0023] The method for preparing the solid electrolyte as described above, wherein the heat treatment is performed in a closed environment;
[0024] and / or, the sublimation temperature of the coating source is less than 500° C.;
[0025] And / or, the heat treatment temperature is 150°C-500°C.
[0026] In a third aspect, the present invention provides a positive electrode sheet, comprising the solid electrolyte as described above or a solid electrolyte prepared by the method for preparing the solid electrolyte as described above.
[0027] In a fourth aspect, the present invention provides a battery, comprising the solid electrolyte as described above, or a solid electrolyte prepared by the method for preparing the solid electrolyte as described above, or a positive electrode sheet as described above.
[0028] The solid electrolyte provided by the present invention can reduce the interface impedance between the solid electrolyte and the electrode material and fill the micro defects and pores on the surface of the solid electrolyte matrix by introducing a coating layer on the surface of the solid electrolyte matrix and using an inorganic substance with a sublimation temperature of less than 500°C as the coating material, with a coating rate greater than or equal to 90%. At the same time, it can prevent the solid electrolyte matrix from being directly exposed to the environment and form chemical bonds with certain metal elements in the solid electrolyte matrix, thereby improving the ionic conductivity retention rate and stability of the solid electrolyte. When applied to a battery, the specific capacity and the first coulombic efficiency of the battery can be improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the technical solutions in the embodiments of the present invention or related technologies, the following briefly introduces the drawings required for use in the embodiments of the present invention or related technologies. Obviously, the drawings described below are only some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0030] Figure 1 a is a SEM image of the solid electrolyte of Example 1 of the present invention, and b is an EDS image of the solid electrolyte of Example 1 of the present invention;
[0031] Figure 2 a is a SEM image of the solid electrolyte of Comparative Example 2 of the present invention, and b is an EDS image of the solid electrolyte of Comparative Example 4 of the present invention;
[0032] Figure 3 This is the XPS spectrum of the solid electrolyte of Comparative Example 2 of the present invention;
[0033] Figure 4 This is the XPS energy spectrum of the solid electrolyte of Example 1 of the present invention. DETAILED DESCRIPTION
[0034] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] In the development of modern energy storage technology, solid-state electrolytes have attracted much attention due to their potential high safety and high energy density. However, existing solid-state electrolyte technology still faces many challenges, limiting its widespread adoption in commercial applications.
[0036] First, the stability of solid electrolytes is particularly prominent. In an environment with high air or humidity, many solid electrolytes are prone to degradation reactions, resulting in a significant decrease in their ionic conductivity retention rate. This instability directly affects the battery's specific capacity and first coulombic efficiency, making it difficult to meet the requirements of high-performance energy storage devices.
[0037] Secondly, traditional coating modification methods also have limitations in improving the performance of solid electrolytes. Although the use of solvents for coating can improve the stability of the electrolyte to a certain extent, it also introduces new problems. For example, solvent residues may cause changes in the chemical properties of the electrolyte or even destroy its structure. In addition, the use of solvents increases production costs and is not conducive to large-scale applications. The solvent-free direct mixing method is prone to poor solid-solid contact, uneven coating, and the uncoated electrolyte is partially exposed to the air, further exacerbating its instability. Although atomic deposition technology can achieve uniform coating effects, its high cost and complex process limit its application in large-scale production.
[0038] Based on this, in the first aspect, the present invention provides a solid electrolyte, comprising a solid electrolyte matrix and a coating layer present on the surface of the solid electrolyte matrix, the coating layer comprising an inorganic substance with a sublimation temperature less than 500°C, for example, it can be 60°C, 70°C, 80°C, 90°C, 100°C, 150°C, 200°C, 250°C, 300°C, 350°C, 400°C, 450°C, 500°C or a range consisting of any two of them; the coverage of the solid electrolyte is greater than or equal to 90%, for example, it can be 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99%, 100% or a range consisting of any two of them.
[0039] The solid electrolyte provided by the present invention has a high ion conductivity retention rate and high stability. When applied to a battery, it can improve the specific capacity and the first coulombic efficiency of the battery. The reason is that the coating layer and the high coverage rate can improve the interface contact between the solid electrolyte and the electrode material. Good interface contact can reduce charge accumulation and interface reaction at the interface, thereby reducing interface impedance, helping to improve the transmission efficiency of ions at the interface, and thus improving the overall ion conductivity retention rate. Inorganic substances with a sublimation temperature of less than 500°C can fill the microscopic defects and pores on the surface of the solid electrolyte matrix during the deposition process. This filling effect can reduce the scattering and trapping effects of ions during the transmission process, thereby improving the ion conductivity retention rate.
[0040] In addition, the inorganic coating layer can achieve uniform coating of the solid electrolyte matrix, and the high coating rate avoids the problem of poor solid-solid contact. The uniform coating layer can effectively protect the electrolyte matrix, prevent it from being directly exposed to the environment, and reduce the impact of environmental factors on the electrolyte performance. Inorganic substances with a sublimation temperature of less than 500°C will form chemical bonds with certain metal elements in the solid electrolyte matrix, further improving the stability of the solid electrolyte in the air, which is conducive to maintaining the structural integrity of the solid electrolyte and reducing obstacles in the ion transmission process, thereby improving the ion conductivity retention rate. The solid electrolyte is applied to the battery to improve the specific capacity and first coulomb efficiency of the battery.
[0041] Therefore, the solid electrolyte provided by the present invention can reduce the interface impedance between the solid electrolyte and the electrode material and fill the micro defects and pores on the surface of the solid electrolyte matrix by introducing a coating layer on the surface of the solid electrolyte matrix and using an inorganic substance with a sublimation temperature less than 500°C as a coating material with a coating rate greater than or equal to 90%. At the same time, it can prevent the solid electrolyte matrix from being directly exposed to the environment, and can form chemical bonds with certain metal elements in the solid electrolyte matrix, thereby improving the ionic conductivity retention rate and stability of the solid electrolyte. When applied to a battery, it can improve the specific capacity and first coulomb efficiency of the battery.
[0042] The coating rate of the solid electrolyte in the present invention can be adjusted by controlling the relationship between the heat treatment temperature and the sublimation temperature of the coating source, as well as the mass ratio of the solid electrolyte matrix to the coating source.
[0043] In some embodiments of the present invention, the thickness of the coating layer is 0.1nm-100nm, for example, it can be 0.1nm, 1nm, 2nm, 5nm, 10nm, 20nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm, 100nm or a range consisting of any two of them, preferably 2nm-20nm.
[0044] The coating layer thickness of the present invention is within the above range, which allows ions to pass through effectively without significantly increasing the resistance of the ion transmission path, which is beneficial to improving the overall ion conductivity retention rate of the solid electrolyte. And the coating layer with suitable thickness can provide sufficient physical and chemical coating to improve the interface stability between the solid electrolyte and the electrode, which is beneficial to prevent interface reaction and solid electrolyte degradation, thereby improving the specific capacity and first coulomb efficiency of the battery. In addition, the coating layer with suitable thickness can effectively isolate the influence of the external environment on the electrolyte, such as the intrusion of moisture and oxygen, and can also provide certain thermal protection to prevent the degradation of the solid electrolyte at high temperature and improve the stability of the solid electrolyte.
[0045] In some embodiments of the present invention, the electronegativity of the bonding elements in the inorganic substance is 2.0-2.8, for example, it can be 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8 or a range consisting of any two thereof.
[0046] It can be understood that the electronegativity of bonding elements in inorganic substances refers to the elements in inorganic substances that bond with metal elements in the solid electrolyte matrix, and the size of the electronegativity can characterize the ability of the element to attract shared electron pairs in chemical bonds.
[0047] The electronegativity of the inorganic substance in the present invention is within the above range, which can reduce the degree of electron loss of the metal element in the solid electrolyte matrix, and the metal element and OH - The binding ability of the solid electrolyte is weak, which can reduce the sensitivity of the solid electrolyte matrix to water, thereby improving the stability of the solid electrolyte. In addition, inorganic substances with appropriate electronegativity can optimize the ion conduction path, because electronegativity affects the electronic structure and bonding characteristics of the material, thereby affecting the migration ability of ions. Appropriate electronegativity can improve the conduction efficiency of ions in the coating layer, that is, improve the ion conductivity retention rate. In turn, the specific capacity and first coulomb efficiency of the battery can be improved.
[0048] In some embodiments of the invention, the coating layer comprises elemental sulfur.
[0049] The coating layer in the present invention includes elemental sulfur, which can protect the solid electrolyte matrix from environmental influences, and is conducive to improving the stability of the solid electrolyte. And elemental sulfur can replace certain elements in the solid electrolyte matrix, and form chemical bonds with the metal elements in the solid electrolyte matrix, further improving the stability of the solid electrolyte in the air. In addition, elemental sulfur can form a good interface contact with the solid electrolyte matrix, reduce the interface impedance, thereby improving the ion transmission efficiency, and then improving the ion conductivity retention rate of the solid electrolyte, and can also fill the microscopic defects and pores on the surface of the solid electrolyte matrix, further improving the ion conductivity retention rate.
[0050] In some embodiments of the present invention, the solid electrolyte matrix includes a halide solid electrolyte.
[0051] Specifically, the chemical composition of the halide solid electrolyte is Li a MX b, wherein M is selected from at least one of Mg, Al, Ga, In, Sb, Bi, Y, Sc, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Zr, Hf, Cr, Fe, Zn and Cd, X is selected from at least one of Cl, Br, I and F, 1≤a≤3, for example, it can be 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.8, 2, 2.2, 2.5, 2.7, 3 or a range consisting of any two thereof, 1≤b≤6, for example, it can be 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6 or a range consisting of any two thereof.
[0052] The solid electrolyte matrix of the present invention comprises a chemical composition of Li a MX b The halide solid electrolyte has a strong ability to migrate lithium ions in the halide lattice, especially in a suitable crystal structure, which is beneficial to improving the ion conductivity retention rate of the solid electrolyte. The M element and the X element can form a stable compound, so that the solid electrolyte is not easy to decompose or have side reactions under battery working conditions, thereby improving the safety and life of the battery. In addition, the M element and the X element can improve the interface compatibility between the solid electrolyte and the electrode material, reduce the interface impedance, and help improve the overall electrochemical performance of the battery.
[0053] In some embodiments of the present invention, M is selected from at least one of Ga, In, Y, Sc, Ho, Yb, Lu, Zr and Hf.
[0054] In some embodiments, X is selected from Cl and / or Br.
[0055] As a preferred solution, when M is selected from at least one of the above elements and X is selected from Cl and / or Br, the ionic conductivity retention rate of the solid electrolyte can be further improved, the safety and life of the battery can be improved, and the overall electrochemical performance of the battery can be improved.
[0056] In some embodiments of the present invention, the difference between the binding energy between the elements of the inorganic substance and the binding energy between the elements of the inorganic substance and the elements of the solid electrolyte matrix is 0.1eV-2.0eV, for example, it can be 0.1eV, 0.5eV, 1.0eV, 1.2eV, 1.6eV, 2.0eV or a range consisting of any two of them.
[0057] In the present invention, the difference between the binding energy between the elements of the inorganic substance and the binding energy between the elements of the inorganic substance and the elements of the solid electrolyte matrix is within the above range, which means that the coating layer forms a chemical bond with certain metal elements in the solid electrolyte matrix, which can improve the stability of the solid electrolyte, help maintain the structural integrity of the solid electrolyte, reduce obstacles in the ion transmission process, and thus improve the ion conductivity retention rate. The solid electrolyte is applied to the battery to improve the specific capacity and the first coulomb efficiency of the battery.
[0058] In some embodiments of the present invention, the ionic conductivity of the solid electrolyte is greater than 0.3 mS / cm, for example, it can be 0.3 mS / cm, 0.4 mS / cm, 0.5 mS / cm, 0.6 mS / cm, 0.7 mS / cm, 0.8 mS / cm, 1 mS / cm, 1.5 mS / cm, 2 mS / cm, 3 mS / cm, 4 mS / cm, 5 mS / cm, 10 mS / cm, 20 mS / cm, 30 mS / cm, 50 mS / cm or a range consisting of any two of them.
[0059] The ionic conductivity of the solid electrolyte in the present invention is greater than 0.3 mS / cm, which means that ions can migrate quickly in the electrolyte, thereby improving the specific capacity and the first coulombic efficiency of the battery.
[0060] In a second aspect, the present invention provides a method for preparing the solid electrolyte as described above, comprising the following steps:
[0061] A raw material system including a solid electrolyte matrix and a coating source is heat-treated and cooled to obtain a solid electrolyte; wherein the heat treatment temperature is greater than the sublimation temperature of the coating source; and the mass ratio of the solid electrolyte matrix to the coating source is (100-1000):1, for example, it can be 100:1, 200:1, 400:1, 500:1, 700:1, 1000:1 or a range consisting of any two of them.
[0062] The preparation method of the solid electrolyte of the present invention is to make the heat treatment temperature greater than the sublimation temperature of the coating source, and limit the mass ratio of the solid electrolyte matrix to the coating source to (100-1000):1, so that the coating source is sublimated into a gaseous state and coated on the surface of the solid electrolyte matrix, that is, gas-solid contact, and then cooled so that the coating source is evenly coated on the surface of the solid electrolyte matrix.
[0063] Specifically, the solid electrolyte matrix and the coating source can be stirred and mixed evenly according to the above-mentioned mass ratio to obtain a mixture, and then the mixture is heat treated, wherein the heat treatment temperature is greater than the sublimation temperature of the coating source and lower than the destruction temperature of the solid electrolyte matrix, and after cooling, the solid electrolyte of the first aspect of the present invention is obtained.
[0064] The preparation method of the solid electrolyte of the present invention does not require the use of solvents and will not destroy the structure of the solid electrolyte matrix. The coating process is gas-solid contact rather than solid-solid contact, and a uniform coating layer can be formed on the surface of the solid electrolyte matrix. The coating layer can form chemical bonds with certain metal elements in the solid electrolyte matrix, and is not a single physical coating. Therefore, the ionic conductivity retention rate and stability of the obtained solid electrolyte can be higher, thereby improving the specific capacity and the first coulombic efficiency of the battery.
[0065] In some embodiments of the present invention, the heat treatment is performed in a closed environment, so that the coating source is not easily diffused to the outside after sublimation, and more coating sources are coated on the surface of the solid electrolyte matrix, which is beneficial to improve the coating rate of the solid electrolyte.
[0066] In a specific implementation, the solid electrolyte matrix and the coating source can be placed in a glass tube, and then the glass tube is vacuum sealed, and the sealed glass tube is heat treated.
[0067] In some embodiments, the sublimation temperature of the coating source is less than 500°C, for example, it can be 60°C, 70°C, 80°C, 90°C, 100°C, 150°C, 200°C, 250°C, 300°C, 350°C, 400°C, 450°C, 500°C or a range consisting of any two of them.
[0068] In some embodiments, the heat treatment temperature is 150°C-500°C, for example, 150°C, 200°C, 250°C, 300°C, 350°C, 400°C, 450°C, 500°C or any two thereof.
[0069] In the present invention, the sublimation temperature of the coating source and the temperature of the heat treatment are within the above ranges, which is conducive to the sublimation of the coating source, so that the coating source is smoothly sublimated into a gaseous state and coated on the surface of the solid electrolyte matrix, and then cooled so that the coating source is evenly coated on the surface of the solid electrolyte matrix. It is beneficial to improve the ionic conductivity retention rate and stability of the solid electrolyte, and thus improve the specific capacity and the first coulomb efficiency of the battery.
[0070] In a third aspect, the present invention provides a positive electrode sheet, comprising the solid electrolyte as described above or a solid electrolyte prepared by the method for preparing the solid electrolyte as described above.
[0071] The positive electrode sheet provided by the present invention comprises the above-mentioned solid electrolyte, so the positive electrode sheet is applied to a battery to improve the specific capacity and the first coulombic efficiency of the battery.
[0072] The present invention does not limit the preparation method of the positive electrode sheet. In a specific embodiment, the positive electrode active material, solid electrolyte, conductive agent, binder, etc. can be mixed and dispersed in a solvent to prepare a positive electrode paste. Subsequently, the positive electrode paste is coated on at least one functional surface of the positive electrode current collector. After drying and rolling, a positive electrode sheet including a solid electrolyte inside is obtained according to the present invention. Further, a dispersion liquid including a solid electrolyte can also be prepared, and the dispersion liquid is coated on the surface of the above positive electrode sheet to obtain a positive electrode sheet including a solid electrolyte both inside and on the surface.
[0073] Alternatively, the positive electrode active material, conductive agent, binder, etc. are mixed and dispersed in a solvent to prepare a positive electrode paste, and a dispersion liquid including a solid electrolyte can also be prepared at the same time. Subsequently, the positive electrode paste is coated on at least one functional surface of the positive electrode current collector. After drying, the dispersion liquid is coated on the dried surface, and after drying again, rolling is performed to obtain a positive electrode sheet including a solid electrolyte on the surface according to the present invention.
[0074] The present invention does not make special limitations on the positive electrode active material, conductive agent, and binder. For example, the positive electrode active material is selected from lithium iron phosphate (LiFePO4), lithium cobalt oxide (LiCoO2), lithium nickel cobalt manganese oxide (Li z Ni x Co y Mn 1-x-y O2, where 0.95 ≤ z ≤ 1.05, x > 0, y > 0, 0 < x + y < 1), lithium manganese oxide (LiMnO2), lithium nickel cobalt aluminate (Li z Ni x Co y Al 1-x-y O2, where 0.95 ≤ z ≤ 1.05, x > 0, y > 0, 0.8 ≤ x + y < 1), lithium nickel cobalt manganese aluminate (Li z Ni x Co y Mn w Al 1-x-y-w O2, where 0.95 ≤ z ≤ 1.05, x > 0, y > 0, w > 0, 0.8 ≤ x + y + w < 1), nickel cobalt aluminum tungsten material, lithium-rich manganese-based solid solution positive electrode material (xLi2MnO3·(1 - x)LiMO2, where M = Ni / Co / Mn, 0 < x < 1), lithium nickel cobalt oxide (LiNi x CoyO2, where x > 0, y > 0, x + y = 1), lithium nickel titanium magnesium oxide (LiNi x Ti y Mg zO2, wherein x>0, y>0, z>0, x+y+z=1), lithium nickelate (Li2NiO2), spinel lithium manganate (LiMn2O4), nickel-cobalt-tungsten materials or a combination of several thereof; the conductive agent is selected from at least one of conductive carbon black, Ketjen black, conductive fiber, conductive polymer, acetylene black, carbon nanotubes, graphene, flake graphite, conductive oxides, and metal particles; the binder is selected from at least one of polyvinylidene fluoride and its copolymer derivatives, polytetrafluoroethylene and its copolymer derivatives, polyacrylic acid and its copolymer derivatives, and polyhexafluoropropylene and its copolymer derivatives.
[0075] In a fourth aspect, the present invention provides a battery, comprising the solid electrolyte as described above, or a solid electrolyte prepared by the method for preparing the solid electrolyte as described above, or a positive electrode sheet as described above.
[0076] The battery of the present invention has outstanding performance in terms of specific capacity and first coulombic efficiency.
[0077] The present invention does not limit the preparation method of the battery, for example, the positive electrode sheet, the solid electrolyte, and the negative electrode sheet can be stacked in sequence and then packaged. The positive electrode sheet, the separator, and the negative electrode sheet can also be stacked in sequence to form a basic battery cell, and then the precursor liquid is injected into it, and after sufficient infiltration, the lithium ion battery of the present invention is obtained by baking.
[0078] The positive electrode sheet and the negative electrode sheet in the battery of the present invention have no special requirements relative to the existing positive electrode sheets and negative electrode sheets in the art.
[0079] The technical solution of the present invention is further described below in conjunction with specific embodiments.
[0080] Example 1
[0081] The preparation method of the solid electrolyte of this embodiment comprises the following steps:
[0082] 1) Elemental sulfur (sublimation temperature of 171°C, electronegativity of 2.58) and solid electrolyte matrix Li3YCl6 are stirred and mixed uniformly to obtain a mixture; wherein the mass ratio of the solid electrolyte matrix Li3YCl6 to the coating source elemental sulfur is 700:1.
[0083] 2) Put the mixture into a glass tube, vacuum seal the glass tube, heat treat the sealed glass tube containing the mixture, wherein the heat treatment temperature is 200°C, and obtain a solid electrolyte after cooling. The solid electrolyte includes a solid electrolyte matrix Li3YCl6 and a coating layer of elemental sulfur existing on the surface of the solid electrolyte matrix Li3YCl6. The thickness of the coating layer is 5nm, the coverage of the solid electrolyte is 95%, and the ion conductivity is 0.6mS / cm. In the XPS spectrum, the binding energy of the SS bond in elemental sulfur is 164.0eV, and the binding energy of the SY bond formed by elemental sulfur and the solid electrolyte matrix is 163.0eV. The difference in binding energy between the two is 1.0eV.
[0084] Example 2
[0085] The preparation method of the solid electrolyte of Example 2 is basically the same as that of Example 1, except that the solid electrolyte matrix is changed to Li3InCl6, and the mass ratio of the solid electrolyte matrix Li3InCl6 to the coating source elemental sulfur is changed to 600:1.
[0086] Example 3
[0087] The preparation method of the solid electrolyte of Example 3 is basically the same as that of Example 1, except that the solid electrolyte matrix is changed to Li2ZrCl6, and the mass ratio of the solid electrolyte matrix Li2ZrCl6 to the coating source elemental sulfur is changed to 500:1.
[0088] Example 4
[0089] The preparation method of the solid electrolyte in Example 4 is basically the same as that in Example 1, except that the mass ratio of the solid electrolyte matrix Li3YCl6 coating source elemental sulfur is changed to 400:1.
[0090] Example 5
[0091] The preparation method of the solid electrolyte in Example 5 is basically the same as that in Example 1, except that the mass ratio of the solid electrolyte matrix Li3YCl6 coating source elemental sulfur is changed to 900:1.
[0092] Example 6
[0093] The preparation method of the solid electrolyte of Example 6 is basically the same as that of Example 1, except that the mass ratio of the solid electrolyte matrix Li3YCl6 coating source elemental sulfur is changed to 1000:1.
[0094] Example 7
[0095] The preparation method of the solid electrolyte in Example 7 is basically the same as that in Example 1, except that the mass ratio of the solid electrolyte matrix Li3YCl6 coating source elemental sulfur is changed to 100:1.
[0096] Example 8
[0097] The preparation method of the solid electrolyte in Example 8 is basically the same as that in Example 1, except that the mass ratio of the solid electrolyte matrix Li3YCl6 coating source elemental sulfur is changed to 10:1.
[0098] Example 9
[0099] The preparation method of the solid electrolyte of this embodiment comprises the following steps:
[0100] 1) Elemental iodine (sublimation temperature of 114°C, electronegativity of 2.66) and solid electrolyte matrix Li3YCl6 are stirred and mixed uniformly to obtain a mixture; wherein the mass ratio of the solid electrolyte matrix Li3YCl6 to the coating source elemental iodine is 500:1.
[0101] 2) The mixture is heat treated at a temperature of 200°C, and a solid electrolyte is obtained after cooling. The solid electrolyte includes a solid electrolyte matrix Li3YCl6 and a coating layer of elemental iodine on the surface of the solid electrolyte matrix Li3YCl6, the coating layer has a thickness of 15nm, the coverage of the solid electrolyte is 100%, and the ion conductivity is 0.8mS / cm. In the XPS spectrum, the II bond in elemental iodine has an I 3d5 / 2 binding energy of 620.6eV, and the IY bond formed by elemental iodine and the solid electrolyte matrix has an I 3d5 / 2 binding energy of 618.8eV, and the difference in binding energy between the two is 0.8eV.
[0102] Example 10
[0103] The method for preparing the solid electrolyte of Example 10 comprises the following steps:
[0104] 1) Stirring and mixing elemental sulfur (sublimation temperature is 171°C) and solid electrolyte matrix Li3YCl6 to obtain a mixture; wherein the mass ratio of the solid electrolyte matrix Li3YCl6 to the coating source elemental sulfur is 500:1.
[0105] 2) Add solvent xylene to the mixture, mix well and then dry at 200°C to obtain a solid electrolyte.
[0106] Embodiment 11
[0107] The preparation method of the solid electrolyte in Example 11 is basically the same as that in Example 1, except that the mixture is placed in a crucible for heat treatment.
[0108] Comparative Example 1
[0109] The solid electrolyte of Comparative Example 1 is Li3YCl6 and is not coated.
[0110] Comparative Example 2
[0111] The preparation methods of the solid electrolytes of Comparative Example 2 and Example 1 are basically the same, except that the heat treatment temperature is changed to 80° C., which is lower than the sublimation temperature of elemental sulfur.
[0112] Comparative Example 3
[0113] The preparation method of the solid electrolyte of Comparative Example 3 comprises the following steps:
[0114] 1) Dissolve the polymer PI in the oily solvent NMP to form a solution, and the concentration of PI in the solution is 1wt%;
[0115] 2) adding a halide solid electrolyte Li3YCl6 to the above solution to form a solid electrolyte suspension, wherein the solid content of the halide solid electrolyte Li3YCl6 in the solid electrolyte suspension is 65wt%;
[0116] 3) Spray drying is adopted and the drying temperature is controlled at 140°C to obtain a polymer-coated halide electrolyte after drying.
[0117] Comparative Example 4
[0118] The preparation method of the solid electrolyte of Comparative Example 4 comprises the following steps:
[0119] 1) adding 1 part by weight of ammonium fluoride to 100 parts by weight of Li3YCl6 halide solid electrolyte, and mechanically stirring at 25°C for 0.5 hour to obtain a core-shell halide solid electrolyte precursor;
[0120] 2) The obtained precursor was heat treated at 220℃ for 6h under closed conditions, with a temperature of 1℃min -1 The cooling rate is cooled to room temperature, wherein the ammonium fluoride is thermally decomposed to generate hydrogen fluoride gas which reacts with the Li3YCl6 halide solid electrolyte to obtain a core-shell Li3YCl6 halide solid electrolyte coated with LiF.
[0121] Test example:
[0122] 1. Thickness of coating layer: obtained by transmission electron microscopy or high-power scanning electron microscopy.
[0123] 2. Electronegativity of inorganic substances: an inherent property of matter, which can be directly queried through the chemical periodic table.
[0124] 3. Binding energy: obtained through XPS characterization.
[0125] 4. Coverage: The atomic concentration of each element on the sample surface is calculated based on the peak area of each element obtained from the XPS spectrum and the element correction information. Coverage = concentration of coating layer element / (concentration of coating layer element + concentration of each element in the solid electrolyte matrix). Taking Example 1 as an example, coverage = concentration of S element / (concentration of S element + concentration of Li element + concentration of Y element + concentration of Cl element).
[0126] 5. Ionic conductivity and ionic conductivity retention rate: 200 mg of solid electrolyte was placed in a solid mold, and a pressure of 3 tons was used to press the tablets, and the pressure was maintained for 3 minutes. Then, a carbon-coated aluminum foil was attached to each side of the pressed solid electrolyte sheet as a current collector, and the battery was assembled and pressurized on the outside. The test method was the AC impedance method, and the test frequency was 10MHz-1Hz. The ionic conductivity P1 of the solid electrolyte was obtained.
[0127] After exposure to a dew point of 40°C for 24 h, the ionic conductivity of the solid electrolyte was tested again to be P2, and the ionic conductivity retention rate = (P1-P2) / P1.
[0128] 6. Specific capacity and first coulombic efficiency: Batteries were prepared using the solid electrolytes obtained in the examples and comparative examples (after exposure to air), specifically comprising: mixing the solid electrolyte with the ternary positive electrode material Ni83 in a mass ratio of 3:7 to obtain a positive electrode composite material; using In alloy as the negative electrode material; weighing a certain amount of solid electrolyte, pouring it into a battery mold, pressing it into a sheet under a certain pressure to obtain a solid electrolyte layer, and placing the solid electrolyte layer between the positive electrode sheet formed by the positive electrode composite material and the negative electrode sheet formed by the negative electrode material to obtain a battery.
[0129] At 25℃, charge to 4.5V at a constant current rate of 0.1C / 1C, then charge at a constant voltage rate of 4.5V to a current of 0.05C. The charge capacity at this time is recorded as the first cycle charge capacity. After that, let it stand for 5 minutes, and then discharge at a constant current rate of 0.1C / 1C to a voltage of 2.5V. The discharge capacity this time is recorded as the first cycle discharge capacity of the battery. The discharge capacity / charge capacity obtained is the first coulomb efficiency.
[0130] Figure 1 a is a SEM image of the solid electrolyte of Example 1 of the present invention, and b is an EDS image of the solid electrolyte of Example 1 of the present invention.
[0131] from Figure 1 It can be seen that in the solid electrolyte of Example 1, elemental sulfur is uniformly coated on the surface of the halide solid electrolyte matrix.
[0132] Figure 2a is a SEM image of the solid electrolyte of Comparative Example 2 of the present invention, and b is an EDS image of the solid electrolyte of Comparative Example 4 of the present invention.
[0133] from Figure 2 It can be seen that in the solid electrolyte of Comparative Example 2, the distribution of elemental sulfur is uneven and is not coated on the surface of the halide solid electrolyte matrix.
[0134] Figure 3 This is the XPS energy spectrum of the solid electrolyte of Comparative Example 2 of the present invention.
[0135] Figure 4 This is the XPS energy spectrum of the solid electrolyte of Example 1 of the present invention.
[0136] from Figure 3 and Figure 4 It can be seen that the 2p3 / 2 binding energy of the sulfur element in the solid electrolyte of Comparative Example 2 is 164.0 eV (corresponding to the SS bond in elemental sulfur), and the 2p3 / 2 binding energy of the sulfur element in the solid electrolyte of Example 1 is 163.0 eV (corresponding to the SY bond formed by elemental sulfur and halide), and the difference between the two is 1.0 eV.
[0137] Table 1
[0138]
[0139] As can be seen from Table 1, the solid electrolyte provided by the present invention can reduce the interface impedance between the solid electrolyte and the electrode material and fill the microscopic defects and pores on the surface of the solid electrolyte matrix by introducing a coating layer on the surface of the solid electrolyte matrix and using an inorganic substance with a sublimation temperature of less than 500°C as a coating material with a coating rate greater than or equal to 90%. At the same time, it can prevent the solid electrolyte matrix from being directly exposed to the environment, and can form chemical bonds with certain metal elements in the solid electrolyte matrix, thereby improving the ionic conductivity retention rate and stability of the solid electrolyte. When applied to a battery, the specific capacity and the first coulombic efficiency of the battery can be improved.
[0140] Finally, it should be noted that those skilled in the art will readily conceive of other embodiments of the present invention after considering the specification and practicing the invention disclosed herein. The present invention is intended to cover any variations, uses or adaptations of the present invention, which follow the general principles of the present invention and include common knowledge or customary technical means in the art not disclosed by the present invention, are not limited to the precise structure described above and shown in the drawings, and may be modified and changed in various ways without departing from the scope thereof. The scope of the present invention is limited only by the appended claims.
Claims
1. A solid electrolyte, characterized in that It comprises a solid electrolyte matrix and a coating layer present on the surface of the solid electrolyte matrix, wherein the coating layer comprises an inorganic substance having a sublimation temperature of less than 500° C.; The coverage rate of the solid electrolyte is greater than or equal to 90%.
2. The solid electrolyte according to claim 1, characterized in that The coating layer has a thickness of 0.1 nm to 100 nm, preferably 2 nm to 20 nm.
3. The solid electrolyte according to claim 1 or 2, characterized in that The electronegativity of the bonding elements in the inorganic substance is 2.0-2.
8.
4. The solid electrolyte according to any one of claims 1 to 3, characterized in that The coating layer includes elemental sulfur.
5. The solid electrolyte according to any one of claims 1 to 4, characterized in that The solid electrolyte matrix includes a halide solid electrolyte.
6. The solid electrolyte according to claim 5, characterized in that The chemical composition of the halide solid electrolyte is Li a MX b , wherein M is selected from at least one of Mg, Al, Ga, In, Sb, Bi, Y, Sc, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Zr, Hf, Cr, Fe, Zn and Cd, X is selected from at least one of Cl, Br, I and F, 1≤a≤3, 1≤b≤6.
7. The solid electrolyte according to claim 6, characterized in that The M is selected from at least one of Ga, In, Y, Sc, Ho, Yb, Lu, Zr and Hf; And / or, X is selected from Cl and / or Br.
8. The solid electrolyte according to any one of claims 1 to 7, characterized in that The difference between the binding energy between the elements of the inorganic substance and the binding energy between the elements of the inorganic substance and the elements of the solid electrolyte matrix is 0.1 eV-2.0 eV.
9. The solid electrolyte according to any one of claims 1 to 8, characterized in that The ionic conductivity of the solid electrolyte is greater than 0.3 mS / cm.
10. A method for preparing a solid electrolyte according to any one of claims 1 to 9, characterized in that: The following steps are involved: Heat treating a raw material system including a solid electrolyte matrix and a coating source, and obtaining the solid electrolyte after cooling; Wherein, the temperature of the heat treatment is greater than the sublimation temperature of the coating source; The mass ratio of the solid electrolyte matrix to the coating source is (100-1000):
1.
11. The method for preparing a solid electrolyte according to claim 10, characterized in that: The heat treatment is carried out in a closed environment; and / or, the sublimation temperature of the coating source is less than 500° C.; And / or, the heat treatment temperature is 150°C-500°C.
12. A positive electrode sheet, characterized in that: A solid electrolyte comprising the solid electrolyte according to any one of claims 1 to 9 or a solid electrolyte prepared by the preparation method of the solid electrolyte according to claim 10 or 11.
13. A battery, characterized in that: A solid electrolyte comprising the solid electrolyte according to any one of claims 1 to 9 or a solid electrolyte prepared by the method for preparing the solid electrolyte according to claim 10 or 11 or a positive electrode sheet according to claim 12.
Citation Information
Cited By
Sulfide electrolyte material, solid electrolyte, electrode plate, battery cell or solid-state battery
CN120581683A
Solid electrolyte material and preparation method and application thereof
CN120878956A
Solid-state electrolyte material, preparation method therefor, and use thereof
CN120878956B
Solid-state electrolyte, and preparation method therefor and use thereof
WO2026157320A1